Effects of Cardiac Rehabilitation on Physical Fitness, Physical Function, and Self-reported Outcomes in Patients ≥80 yr: A RANDOMIZED CONTROLLED TRIAL. Issue 5 (31st March 2022) - Brosved, Madeleine; Hirlekar, Geir; Philip Wigh, Julia; Sundberg, Helen; Zidén, Lena; Karlsson, Thomas; Albertsson, Per; Bäck, Maria
Abstract : Patients with an acute coronary syndrome ≥80 yr were randomized to an exercise-based cardiac rehabilitation program or to a control group for 4 mo. The exercise group improved in walking distance, muscle endurance, physical function, and patient-reported outcomes measures but not in peak cardiorespiratory fitness, compared with the control group. Abstract : Purpose: The beneficial effects of exercise-based cardiac rehabilitation (CR) after an acute coronary syndrome (ACS) are well known, but patients ≥80 yr have been less studied. The aim was to evaluate the effects of CR on patients with ACS ≥80 yr on peak cardiorespiratory fitness (CRF), physical function, and patient-reported outcome measures (PROMs) compared with a control group. Methods: A total of 26 patients with ACS, median age 82 (81, 84) yr, were randomized to hospital-based CR combined with a home-based exercise program (CR group) or to a control group (C) for 4 mo. Outcomes were assessed at baseline and 4 mo and included the peak CRF (primary outcome), 6-min walk test (6MWT), muscle endurance, Timed Up and Go (TUG), Short Physical Performance Battery (SPPB), one-leg stand test, and PROMs. Results: There were no significant differences between the groups in peak CRF. The CR group improved significantly in terms of the 6MWT ( P = .04), isotonic muscle endurance ( P < .001), one-leg stand test ( P = .001), SPPB total score ( P =.03), Activities-specific Balance Confidence ( P =.01), and anxiety ( P =.03), as compared with C. There were no significant intergroup differences in the TUG, the self-reported health question or depression. Conclusions: Patients with ACS ≥80 yr improved in walking distance, muscle endurance, physical function, and PROMs, but not in peak CRF, by participating in a CR program. These results suggest an increased referral to CR for this growing group of patients to enable preserved mobility and independence in daily living, but this needs to be confirmed in larger studies.